Erectile Dysfunction in Man with Hyperprolactinemia, Obesity and Genetic Abnormality 46XYinv(9)(p11q13) - Rossy Sintya Marthasari (Indonesian Andrology and Biomedical Journal, 2022)
Background: A good erectile function and normal sexual arousal are indicators of male health. Impaired sexual function due to loss of libido and erectile dysfunction can interfere with quality of life and relationships with partners. Erectile dysfunction can be caused by vasculogenic, endocrinopathy, hormonal imbalance, neurogenic, trauma, iatrogenic and also due to psychological causes. This research to understand and overcome the problems related to sexual function in man with genetic abnormality. Case: A 32-year-old patient came for a sperm analysis examination because he was planning to get married soon. At first, there were no sexual problems complained of but the patient admitted that he was not too much interested in sexual matters since he was young. Nocturnal and morning erection happened rarely. Puberty at 15 years old and currently in a relationship with a woman and planning to get married. At this time libido was good. There was no history of mumps and orchitis. From the physical examination, it was found that the height was 180 cm, weight was 100 kg, and the arm span was 186 cm. waist circumference 104 cm. It means that he was obese. Other physical examinations were within normal limits. Examination of the genitalia showed testicle size of 4 cc right and 4 cc left and soft in consistency. Penis size 8 cm in stretched condition. Sperm analysis showed azoospermia. Cytogenetic examination showed 46XY inv(9)(p11q13) and no Klinefelter syndrome was found. Hormone examination results showed LH 11.92 mIU/ml, FSH 30.29 mIU/ml.He showed hyperprolactinemia 25.89 ng/ml, estradiol 16 pg/ml and total testosterone 2.33 ng/ml. HbA1c 5,9 %. Discussion: The patient was treated with cabergoline 0.25 mg 3 times a week and to overcome hormone imbalance ,we used letrozole 2.5 mg once a day for 2 months.After two months have passed, there is an increase in sexual arousal, morning erections occur at least 4 days a week, erections begin to improve. weight 94 kg, arm span 186 cm. waist circumference 99 cm. Other physical examinations were within normal limits. Examination of the genitalia showed testicle size of 5 cc right and 5 cc left and soft in consistency.Recent investigations showed LH 7.89 mIU/ml, FSH 14.53 mIU/ml, prolactin 15.00 ng/ml, estradiol 10 pg/ml and total testosterone 1.69 ng/ml. Until now, evaluation and treatment is still ongoing. Conclusion: Management of erectile dysfunction can not only be seen from one side but also requires a holistic and multidisciplinary approach. Risk factors that can cause erectile dysfunction problems must be assessed and controlled every single cause. The goal of erectile dysfunction management is not only for sexual satisfaction but also to improve fertility and quality of life.